Innovation in small family firms - Rondi, Emanuela; Sciascia, Salvatore; De Massis, Alfredo (Piccola Impresa / Small Business, 2020)
Research on innovation in family firms has flourished in the last decades. Nevertheless, most of the current understanding has been developed by studying large organizations, leaving the specific challenges and opportunities of innovating in small family firms still untapped. This introductory article summarizes the studies included in the special issue and integrates their contributions by uncovering four types of innovation that allow small family firms to overcome the liability of smallness. Finally, we suggest directions for future research.